Cell surface glycoproteins on cells of the immune system - Barclay, Neil (Henry Stewart Talks, 2007)
Lymphocyte cell surface, Membrane proteins, Identification of interactions, Protein microarrays, Monoclonal antibodies, Recombinant proteins, Characterization of interactions at a molecular level, Reaction kinetics, Protein structure, Role of engagement, Role in disease and potential therapies
Reviewed at 2022/04/12